Dampak Integrasi, Merger dan Konglomerasi Terhadap Risiko Persaingan dan Stabilitas Perekonomian - Dea Nurseptianingsih; Estri Nuraini Hidami; Giska Tri Wida Mulyani; Naerul Edwin Kiky Aprianto; Yuda Restu Prasetya (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
This article analyzes the impact of integration, mergers, and conglomeration on competition risk and economic stability using a literature review approach. The background of this research highlights the increasing prevalence of corporate mergers that may lead to unhealthy competition risks and economic instability. The study aims to identify the characteristics, impacts, and implications of integration, mergers, and conglomeration strategies within the context of market structure, corporate behavior, and performance. The research method employs a qualitative approach by collecting secondary data from journals, e-books, and relevant documents. Data analysis is conducted descriptively-qualitatively by examining the relationship between market structure, corporate behavior, and economic performance through the Structure-Conduct-Performance (SCP) analytical framework. Findings indicate that integration, mergers, and conglomeration have complex effects on business competition. The merging process can reduce the number of competitors, increase the dominance of large firms, and potentially create monopolistic practices. The SCP analysis reveals that changes in market structure through corporate consolidation significantly affect economic behavior and performance. The article emphasizes the need for effective regulation and oversight to minimize negative impacts, protect healthy competition, and maintain economic stability. The conclusion offers deep insights into the dynamics of business integration and its implications for market structure, behavior, and performance.